15 The importance of staying on the call: recognition of cardiac arrest after initial dispatch. (21st May 2017) - Ball, S; Whiteside, A; Inoue, M; Bray, J; Fatovich, DM; Cameron, P; Williams, T; Smith, K; O'Halloran, KL; Brink, D; Perkins, GD; Tohira, H; et al.
Abstract : Aim: We compared survival in out-of-hospital cardiac arrest (OHCA) cases recognised at initial dispatch ("primary recognition") with those subsequently recognised as OHCA ?("secondary recognition") and those not recognised as OHCA ("non-recognition"). Methods: We analysed cases of paramedic-confirmed OHCA in Perth, Western Australia (WA), from January 2014 to December 2015. We excluded traumatic OHCA, paramedic-witnessed arrests, and cases where paramedics did not attempt resuscitation. Emergency ambulance calls in WA are processed using the Medical Priority Dispatch System, via ProQA software. We analysed the ProQA data of each call for the presence of OHCA-specific dispatch codes (including code revisions) and call-taker instructions for cardiopulmonary resuscitation (CPR). Results: Among 1430 cases of OHCA, 84% (n=1195) were recognised by call-takers as OHCA. Of the 1195 recognised cases, 32% (n=386) were identified through secondary recognition. Survival to 30 days was significantly higher among cases with secondary recognition (13.2%) than among cases with primary recognition (7.9%) and non-recognised cases (7.7%) (p=0.008). More than half of all cases of secondary recognition were initially dispatched as Unconscious/Fainting patient. Conclusion: Nearly one third of call-taker recognition of OHCA occurs after initial dispatch. The higher survival probability of patients recognised by secondary recognition is consistent with those patients arresting more recently relative to the timing of the call. For many cases of OHCA, the call-taker's ability to stay on the call and remain alert to the possibility of OHCA may strengthen the chain of survival. Conflict of interest: A. Whiteside and D. Brink receive full salary support, and P. Bailey, M. Inoue and J. Finn receive partial salary support from St John Ambulance. Funding: Funding for this research was received from an Australian NHMRC (National Health and Medical Research Centre) Partnership Project: #1076949 'Improving ambulance dispatch to time-critical emergencies'. J. Finn. and J. Bray receive partial salary support from the NHMRC 'Aus-ROC' Centre for Research Excellence #1029983. J. Bray receives salary support from an NHMRC/NHF (National Heart Foundation) Early Career Fellowship.